Is acupuncture safe in the ICU? A systematic review and meta-analysis - Ben-Arie, Eyal; Lottering, Bernice Jeanne; Chen, Fang-Pey; Ho, Wen-Chao; Lee, Yu-Chen; Inprasit, Chanya; Kao, Pei-Yu (Frontiers in Medicine, 2023)
Background and purpose The safety of interventions for critically ill patients is a crucial issue. In recent years, several studies have treated critically ill patients with acupuncture. However, the safety of acupuncture in this setting remains to be systematically measured. Methods In May 2022, the electronic databases of PubMed and the Cochrane Library were searched for studies comparing acupuncture interventions to control interventions in critically ill patients. Study outcomes examined the incidence of severe adverse events (AEs), minor AEs, adverse reactions, ICU stays, and 28-day mortality. Results A total of 31 articles were analyzed, and no serious AEs related to acupuncture treatment were identified. No significant differences were found between the groups in the meta-analysis of minor AEs (risk ratio [RR] 5.69 [0.34, 96.60], P = 0.23, I2 = 76%). A reduced risk in the incidence of adverse reactions following acupuncture intervention was evidenced (RR 0.33 [0.22, 0.50], P = 0.00001, I2 = 44%). The patients in the acupuncture arm spent significantly less time in the intensive care unit (ICU) (Mean difference −1.45 [−11.94, −10.97], P = 0.00001, I2 = 56%) and also exhibited lower 28-day mortality rates (odds ratio 0.61 [0.48, 0.78], P = 0.0001, I2 = 0%). Conclusion There is no evidence to indicate a higher risk of severe or minor AEs in patients who receive acupuncture. Acupuncture demonstrated favorable results in both ICU stay and 28-day mortality measurements, in addition to presenting with fewer adverse reactions compared to routine ICU care. However, the low certainty of the evidence resulting from a high risk of bias in the included studies merits substantial consideration, and further research is still warranted. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=142131, identifier: CRD42020142131.